Editing syntactic-semantic information of adjectives in the WordNet.Br database - Di Felippo, Ariani; Dias-da-Silva, Bento Carlos (Proceedings of the Brazilian Symposium in Information and Human Language Technology (STIL); 2004: Proceedings of the 2nd Workshop in Information and Human Language Technology, 2004)
This paper proposes the formal inclusion of the “argument structure” and the “subcategorization frame” of adjectives in the Wordnet.Br lexical database. The conclusion outlines such an extension.